PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VI SDN 026 PADANG MUTUNG - Zamandri '; Hendri Marhadi; Syahrilfuddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study departed from low yields six grade social sciences students of SDN 026 Padang Mutung with an average value of 58.45 (KKM 70). The purpose of this study is to improve student learning outcomes social sciences six grade SDN 026 Padang Mutung with the implementation of cooperative learning model type Make A Match. This research is a class act consisting of two cycles The subjects were students of class VI SDN 026 Padang Mutung the school year 2015/2016 the number of students whict amounted to 22 people consisting of 12 male students and 10 female students. Based on the result an analysis the observation of  teachers and students' activity sheet has increased at every meeting. Teachers activity with the implementation of cooperative make a match type learning model at the first meeting of the first cycle was 75% (good) and the second meeting of the first cycle was 87.50% (very good). In the second cycle, Teachers activity at the first meeting amounted to 91.67% (very good) and the second meeting amounted to 95.83% (very good). Students activity at the first meeting of the first cycle was 70.83% (good) and the second meeting was 87.50% (very good). The second meeting was 95.83% (very good). Social sciences student learning outcomes prior to the application of cooperative learning model of Make A Match has an average value of 58.45, after the implementation of cooperative learning model of Make A Match Type average student learning outcomes increased in UH I was70, 90 with a percentage improve of 21.31% , UH II was average student learning outcomes improve 80.00, with a percentage improve 36.86%. Based on this it can be concluded that the application of the model of Cooperative Learning Make A Match can improved learning outcomessocial sciences six grade SDN 026 Padang Mutung. Key Words: Cooperative Learning Model Type Make A Match, Social Sciences  Studies                   Students Achievement